Regulation of electrolyte transport with IL-1β in rabbit distal colon - F. R. Homaidan; H. Desai; L. Zhao; G. Broutman; R. Burakoff (Hindawi Limited, 1995)
Interletrkin-1β levels are elevated in inflammatory bowel disease. In this study the mechanism by which interleukin-1β affects electrolyte transport in the rabbit distal colon, was investigated. Interleukin-1β caused a delayed increase in short-circuit current (Isc) which was attributed to protein synthesis since the effect was inhibited by cycloheximide. The interleukin-1β induced increase in Isc was not affected by amiloride treatment but was completely inhibited by bumetanide or in chloride-free buffer and by indomethacin. Prostaglandin E2 levels increased in tissue treated with interleukin-1β, but this increase was reversed by cycloheximide. These data suggest that interleukin-1β causes its effect via a yet to be identified second messenger, by increasing chloride secretion through a prostaglandin E2 mediated mechanism.